Virtual obstetric psychoprophylaxis associated with maternal perinatal outcomes at Aurelio Díaz Ufano Hospital, 2021 - Cupe Medina, Lizbeth Rossemery (2025)
Introduction. Virtual obstetric psychoprophylaxis enhances prenatal care by improving maternal and neonatal health outcomes. Objectives. To evaluate virtual obstetric psychoprophylaxis and its association with maternal and perinatal outcomes. Methods. An observational, descriptive, and correlational study was conducted at the EsSalud Aurelio Díaz Ufano Hospital (Lima, Peru) from September 2020 to September 2021. A total of 132 nulliparous pregnant women without comorbidities were included, divided into two groups: 66 who received virtual psychoprophylaxis and 66 who did not. Non-probabilistic convenience sampling was applied. Data were collected from electronic medical records and labor ward logs. Statistical analysis was performed using SPSS v22, employing Pearson’s chi-square and Fisher’s exact test, with statistical significance set at p<0.05. Variables included sociodemographic and obstetric characteristics, labor outcomes, and neonatal parameters. Results. Women receiving virtual psychoprophylaxis showed a higher rate of spontaneous labor onset (94.0%), lower use of pharmacologic interventions (6.0%), reduced perineal tears (18.0%), and less prolonged active labor (18.0%). Among newborns, 94.0% had a birth weight between 2 500 and 3 999 g, 100% had normal APGAR scores, 94.0% experienced early skin-to-skin contact, 92.0% underwent delayed umbilical cord clamping, and 92.0% initiated early breastfeeding. A statistically significant association was found between virtual psychoprophylaxis and improved maternal-perinatal outcomes (p<0.05). Conclusion. Virtual obstetric psychoprophylaxis is associated with better maternal and perinatal outcomes and represents an effective alternative for pregnant women without access to in-person education programs.